Identifying oxidized lipid mediators as prognostic biomarkers of chronic posttraumatic headache. Issue 12 (December 2020) - Domenichiello, Anthony F.; Jensen, Jennifer R.; Zamora, Daisy; Horowitz, Mark; Yuan, Zhi-Xin; Faurot, Keturah; Mann, J. Douglas; Mannes, Andrew J.; Ramsden, Christopher E.
Abstract : Abstract: Chronic posttraumatic headache (PTH) is among the most common and disabling sequelae of traumatic brain injury (TBI). Current PTH treatments are often only partially effective and have problematic side effects. We previously showed in a small randomized trial of patients with chronic nontraumatic headaches that manipulation of dietary fatty acids decreased headache frequency, severity, and pain medication use. Pain reduction was associated with alterations in oxylipins derived from n-3 and n-6 fatty acids, suggesting that oxylipins could potentially mediate clinical pain reduction. The objective of this study was to investigate whether circulating oxylipins measured in the acute setting after TBI could serve as prognostic biomarkers for developing chronic PTH. Participants enrolled in the Traumatic Head Injury Neuroimaging Classification Protocol provided serum within 3 days of TBI and were followed up at 90 days postinjury with a neurobehavioral symptom inventory (NSI) and satisfaction with life survey. Liquid chromatography-tandem mass spectrometry methods profiled 39 oxylipins derived from n-3 docosahexaenoic acid (DHA), and n-6 arachidonic acid and linoleic acid. Statistical analyses assessed the association of oxylipins with headache severity (primary outcome, measured by headache question on NSI) as well as associations between oxylipins and total NSI or satisfaction with life survey scores. Among oxylipins, 4-hydroxy-DHA and 19, 20-epoxy-docosapentaenoate (DHA derivatives) were inversely associated with headache severity, and 11-hydroxy-9-epoxy-octadecenoate (a linoleic acid derivative) was positively associated with headache severity. These findings support a potential for DHA-derived oxylipins as prognostic biomarkers for development of chronic PTH. Abstract : Supplemental Digital Content is Available in the Text.Oxylipins derived from docosahexaenoic acid (a component of fish oil) are potential prognostic, pharmacodynamic biomarkers of chronic posttraumatic headache in traumatic brain injury patients.